2017
DOI: 10.18632/oncotarget.18061
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C is associated with large cerebral artery stenosis in acute ischemic stroke

Abstract: Large cerebral artery stenosis is a major cause of acute ischemic stroke (AIS); however, the correlation between serum cystatin C (CysC) and the stenosis of large cerebral arteries in patients with AIS has not been established. We performed a retrospective review of acute ischemic stroke patients, who were examined by cerebral digital subtraction angiography(DSA). Participants (252 cases) included 131 patients without stenosis and 121 patients with large cerebral artery stenosis. Serum CysC levels in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…Therefore, CysC acts as a good biomarker for acute ischemic stroke. Going with our result, Xu and colleagues [6] noticed that elevated CysC levels were strongly associated with stroke. Yang and colleagues [7] have similar results and hypothesized that Cyst C plays an important role in the pathogenesis of atherosclerosis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, CysC acts as a good biomarker for acute ischemic stroke. Going with our result, Xu and colleagues [6] noticed that elevated CysC levels were strongly associated with stroke. Yang and colleagues [7] have similar results and hypothesized that Cyst C plays an important role in the pathogenesis of atherosclerosis.…”
Section: Discussionsupporting
confidence: 82%
“…Matching with our study result, Xiao and colleagues [8] and Huang and colleagues [16] found that CysC levels were not correlated with serum total cholesterol, high-density lipoprotein, and low-density lipoprotein levels. While on the contrary, Xu and colleagues [6] observed a significant correlation with serum CysC levels and serum triglycerides and cholesterol.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Z. Xu и соавт. [27] показали, что у пациентов с церебральным инсультом и атеросклерозом сонных артерий достоверно повышен уровень цистатина С в плазме крови. Примечательно, что в настоящем исследовании пациенты в исследуемых группах были сопоставимы по параметрам гемодинамики, полу, возрасту, липидному составу крови.…”
Section: Discussionunclassified
“…A recent study has shown that high CysC levels are associated with CHD in type 2 diabetes mellitus patients [10]. Serum CysC is also reported to be independently associated with cerebral artery stenosis in ischemic stroke patients [11]. However, few studies have evaluated the relationship between CysC and vascular complications in type 2 diabetes mellitus patients.…”
Section: Introductionmentioning
confidence: 99%